Foundation Status of Legal Entity That has not Registered in The System Under Administration as Regulation of Minister of Justice and Human Rights No. 5 of 2014 Concerning The Ratification of Legal Entity - Ardy Oktavian; Suwono Suwono (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
The Foundation is a legal entity consisting of wealth are separated and destined to achieve certain objectives in the social, religious, and humanitarian who has no members. Foundation stipulated in Act No. 16 of 2001 as amended by Act No. 28 of 2008 and further stipulated in Government Regulation No. 63 of 2008. The Foundation is a legal entity that can act and take legal actions were legitimate and resulted of law. Wealth foundation has separated, has assets of both movable and immovable which was originally derived from capital or wealth founders who have been separated. The Foundation has a specific purpose which is the implementation of the good values of religious, social, and humanitarian non-profit. The Foundation does not have members and does not have shareholders or its allies. The Foundation is driven by better foundation organ Trustees, Trustees and administrators. Legal risk for organ foundation is not getting a salary, to be convicted, personal property administrators and supervisors can be guaranteed, the attachment foundation board on budgetary basis, the application of the principle of Duty Skill Care for administrators and supervisors, and the implementation of employee activities. The Foundation shall make an annual report and efforts to conduct an examination of the foundation. In article 5 of 2014 concerning the Ratification of the Entity many foundations were re-registered through a system of legal entity through a notary so that the notary has the obligation to register on the foundation filed. So in the implementation strengthen notary deed establishing the foundation when it should be an adjustment but, because of the administrative system there are no legal entities adjustment column notary can only use applications with a choice of establishments column.Keywords: Legal Foundation, Legal Entity Administration System, Legalization Agency.